Clinical Features and Prognostic Factors of Small Cell Lung Cancer：A Retrospective Study in 148 Patients - 蔡茜 罗红兰 高喜璨 熊春锦 童凡 张瑞光 胡豫 伍钢 董晓荣 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
To better understand the outcomes of small cell lung cancer（SCLC）,we examined the clinical features and prognostic factors of SCLC in this study.A total of 148 patients who were diagnosed as having SCLC between January 2009 and December 2013 in Cancer Center of Union Hospital,Wuhan,China,were enrolled and their clinical features and prognostic factors were retrospectively analyzed.Log-rank test and Cox regression model were employed for analysis of prognostic factors.The 1-and 2-year overall survival（OS） rates were 59.7% and 25.7%,respectively,for limited disease（LD） patients whose median survival time（MST） was 16 months.The 1-and 2-year OS rates were 29.5% and 5.3%,respectively,for extensive disease（ED） patients whose MST was 10 months.The univariate analysis and multivariate analysis revealed that age,tumor stage,serum CEA and Ki-67 antigen were significantly correlated to the outcomes of SCLC,and they were significant prognostic factors for SCLC.